2012
DOI: 10.3109/08880018.2012.657767
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of γ-Glutamyl Hydrolase in Chinese Acute Leukemia Children and Identification of a Novel Double Nonsynonymous Mutation

Abstract: γ-Glutamyl hydrolase (GGH) plays a central role in folate metabolism and antifolate action. Polymorphism in the human GGH gene (GGH) was associated with efficacy and side effects of methotrexate for treatment of acute lymphoblastic leukemia (ALL). This study aimed to identify polymorphisms of GGH in Chinese. Seventy-one children with ALL, 25 children with acute myeloid leukemia (AML), and 132 children with nonmalignancy as control were included. Human GGH cDNAs were prepared and analyzed by reverse transcripta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
2
5
3
Order By: Relevance
“…While GGH-452TT genotype was not found in this study, this may well be biased by the moderate sample size. It is indeed a rare variant being only infrequently reported in a Japanese population (one out of 269) [20], in Chinese leukemia children (one in 203) [65], but not found in Mexican paediatric patients with ALL (n = 70) [23]. The prevalence of ITPA-94AC/AA genotypes in Caucasian (15.1%) and Vietnamese (33.9%) children with ALL was in line with previous studies [37,54,58].…”
Section: Discussionsupporting
confidence: 86%
“…While GGH-452TT genotype was not found in this study, this may well be biased by the moderate sample size. It is indeed a rare variant being only infrequently reported in a Japanese population (one out of 269) [20], in Chinese leukemia children (one in 203) [65], but not found in Mexican paediatric patients with ALL (n = 70) [23]. The prevalence of ITPA-94AC/AA genotypes in Caucasian (15.1%) and Vietnamese (33.9%) children with ALL was in line with previous studies [37,54,58].…”
Section: Discussionsupporting
confidence: 86%
“…Frequency of the GGH-401'T' allele in the SI population (29.8%) was significantly lower when compared to West Indians (61%), [28] but it was similar to EUR, North Indian, [23] and Thai populations. [10] In the present study, the frequency of GGH-452'T' allele (16.7%) in SI individuals was significantly higher when compared to Dutch, [22] Japanese, [24] Chinese, [25,26] Brazilian, [27] and Mexican populations, [12] but similar to that found in Puerto Rican [21] and North Indian populations [23] [Table 4].…”
Section: Comparison Of Frequency Of Studied Variants In South Indian Population With Data From the 1000 Genomes Project And Other Studiessupporting
confidence: 83%
“…In the present study, the GGH452'T' allele was not significantly associated with the risk of ALL [Table 2], and our results are in accordance with the previous studies conducted on Mexican [12] and Chinese populations. [25] Furthermore, in the present study, the GGH-401C>T polymorphism was also not associated with the susceptibility to ALL. Our study results are similar to the findings by Koomdee et al in a Thai population, [10] but not in line with a study done on Mexican population where the -401'T' allele was associated with the risk of ALL (P = 0.001).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In another case-control study, Chen et al[50] reported that 452 T allele was significantly associated with increasing rate of hepatotoxicity grade ≥2 [OR=…”
mentioning
confidence: 99%